Negative Racial Encounters and Academic Outcomes of International and Domestic Students in Four Canadian Universities - Grayson, J. Paul (Journal of International Students, 2014)
In Canada, there has been little systematic inquiry into the nature and extent of discrimination against university students and the potential impact of discrimination on educational outcomes. On the basis of an examination of domestic and international students at the University of British Columbia (Vancouver), York (Toronto), McGill (Montreal), and Dalhousie (Halifax), it is argued that with the exception of employment of Chinese origin and Black students, in general, students experience little discrimination on- and off-campus; that the discrimination confronted by students does not systematically correspond to their minority non-minority status; and that discrimination is of little consequence for grade point average and program satisfaction.